Mengukur Kinerja Keuangan UMKM: Peran Human Capital, Literasi Keuangan, dan Adopsi Fintech - Isnaini Anniswati Rosyida; Siti Shoimah; Yerisma Welly; Martin Yehezkiel Sianipar (Journal of Business and Economics Research (JBE), 2026)
This study examines the effect of Human Capital, Financial Literacy, and Financial Technology (FinTech) Adoption on the Financial Performance of Micro, Small, and Medium Enterprises (MSMEs), with Risk Perception serving as a moderating variable. A quantitative research design was employed, and data were collected through questionnaires distributed to 98 MSME actors in Baureno District, Bojonegoro Regency. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings indicate that Human Capital, Financial Literacy, and Financial Technology Adoption each have a positive and significant effect on MSME financial performance. Furthermore, Risk Perception significantly moderates the relationship between FinTech Adoption and Financial Performance in a negative direction, suggesting that higher levels of perceived risk weaken the positive impact of FinTech adoption on business performance. These results underscore the critical role of strengthening human capital capabilities, enhancing financial literacy, and promoting technological adoption to improve MSME performance. However, they also highlight the importance of managing perceived business risks to ensure that the benefits of financial technology can be fully realized